New Spectrophotometric Determination Cefdinir Coupling with Bisphenol A via Various Analytical Methods - Nisreen Kais Abood (Journal of Global Pharma Technology, 2016)
A new three spectrophotometric methods are developed for determination of cefdinir. The first method including conversion the of amine functional group in cefdinir to diazonium ion followed by reaction with reagent Bisphenol A in alkaline medium. Produced azo dye has a Reddish- Orange with absorption intensity at λmax 495 nm. The concentration ranges 1-50 μg/ mL, Beer's law is obeyed, correlation coefficient was 0.9996, molar absorptivity was 0.613×104L.mol-1.cm-1 and the detection limit was 0.194 μg/mL. The Second method was cloud point extraction (CPE) of a trace amount in aqueous solution that product of diazotization followed by measuring with a UV-visible spectrophotometer at λmax 505, purple color. The concentration range obeyed the Beer's law was 0.25-6 μg / mL, correlation coefficient was 0.9995, molar absorptivity was 0.727×105L.mol-1.cm-1, detection limit was 0.036 μg/mL, Pre-concentration factor was 25 and Distribution coefficient(D) was 394.13. Flow injection analysis third methods it is simple for setimation the cefdinir based on the measurement of absorption signal for product resulting from diazotization, all experimental parameters chemical and physical were studied to development and stability the colored of product. Flow injection of 1.5mL/min was pumped and active material was detecting at λ max 495nm. In this the proposed methods were successfully, applied to the estimation Cefdinir in pharmaceutical formulation. The three opposed methods have been applied successfully to the Cefdinir drug in the pharmaceutical formulation.Keywords: Cefdinir, Diazotization, Cloud point extraction, Bisphenol A, Flow Injection Analysis.